Facial Swelling as a Primary Manifestation of Multiple Myeloma - Anju E. Thomas; Seema Kurup; Renju Jose; Cristalle Soman (Case Reports in Dentistry, 2015)
Facial swellings are commonly encountered in the dental office, the cause of which could range from a congenital etiology to an acquired one or it may even be a manifestation of an underlying systemic disease. The clinician must have a thorough knowledge of the various clinical and imaging manifestations and the sites of occurrence of the various conditions to arrive at the appropriate diagnosis. Facial swellings can be classified into different groups which include acute swellings with inflammation, nonprogressive swellings, and slowly or rapidly progressive swellings. The various imaging modalities like CT and MRI are useful for assessing the extent of the swelling as well as evaluating the soft tissue and osseous involvement of the swelling. Multiple myeloma represents clonal proliferation of plasma cells and is a condition in which a facial swelling might be present, though not common. This paper reports a case of a patient with a unilateral facial swelling, which on investigation led to a diagnosis of multiple myeloma.